A comparative study on the quality of protein crystals obtained using the cross-diffusion microbatch and sitting-drop vapor diffusion methods1. Issue 29 (7th August 2015) - Hou, Hai; Wang, Bo; Hu, Shan-Yang; Wang, Jing-Zhang; Zhu, Peng-Fei; Liu, Yue; Wang, Meng-Ying; Yin, Da-Chuan
<x xml:space="preserve">Abstract</x> The protein crystals grown using the cross-diffusion microbatch method exhibited better quality than those grown using the sitting-drop vapor diffusion method.